Study on the Correlation of Skin Advanced Glycation End Products With Diabetic Cardiovascular Autonomic Neuropathy - Fang Y; Dai W; Cao Y (Diabetes, Metabolic Syndrome and Obesity)
Yucheng Fang, Wu Dai, Yonghong Cao Department of Endocrinology, Hefei second People’s Hospital, Hefei, 230011, People’s Republic of ChinaCorrespondence: Yucheng Fang, Email 248839713@qq.comAim: To investigate the correlation of advanced glycation end products (AGEs) with diabetic cardiovascular autonomic neuropathy (DCAN). Factors affecting DCAN and those related to skin AGE accumulation in patients with DCAN were analyzed.Materials and Methods: A total of 192 patients with type 2 diabetes mellitus (T2DM) who were hospitalized in the Department of Endocrinology of Hefei Second People’s Hospital from November 2020 to December 2022 were included and divided into DCAN (n=121) and No_DCAN (n=71) groups based on the results of Ewing test. All patients completed the detection of skin AGEs accumulation. The clinical features of the two groups were analyzed; the factors affecting DCAN were analyzed by multiple logistic regression analysis, and those related to skin AGE accumulation in patients with DCAN were analyzed by Spearman correlation analysis and Pearson correlation analysis.Results: Compared with the No_DCAN group, the combined DR ratio, fasting plasma glucose (FPG), and skin AGEs were increased in the DCAN group (all P< 0.05). Multivariate logistic regression analysis showed that FPG, combined DR, and skin AGEs all affected DCAN (P< 0.05). Spearman correlation analysis showed that skin AGE accumulation in patients with DCAN was correlated with sex (male or female) and the presence of vascular plaques (All P< 0.05). Pearson correlation analysis showed that skin AGE accumulation in patients with DCAN was correlated with age, diabetes course, diastolic blood pressure, uric acid, creatinine and UACR levels (All P< 0.05).Conclusion: Skin AGEs, combined DR and FPG affected DCAN, and skin AGEs, combined DR and FPG were closely related to the incidence of DCAN. Sex (male or female), presence of vascular plaques, age, diabetes course, diastolic blood pressure, uric acid levels, creatinine levels and UCAR levels were correlated with skin AGE accumulation in patients with DCAN.Keywords: diabetic cardiovascular autonomic neuropathy, skin advanced glycation end products